Assortative marriage and intergenerational persistence of earnings: theory and evidence - Santi, Murilo Esteves de (2016)
I study the impact of the changes in the U.S. labor market that took place in the last few decades - such as the increase in the college wage premium and the reduction in the gender wage gap - on the intergenerational persistence of income, with a particular emphasis on the marriage market channel. To motivate my analysis, I document a positive cross-country correlation between intergenerational persistence of income (and education) and educational assortative mating. I then develop an overlapping generations model in which parents invest in their children's education and individuals choose whom they are going to marry, and estimate the model to fit the postwar U.S. data. My results suggest that both of these changes have affected the intergenerational earnings persistence, but that the marriage decision plays only a very small role in these results.